Dermatologist Driven Aesthetic Nail Enhancement - Shikha Bansal; Soni Nanda; Sonal Bansal; Chander Grover (Indian Dermatology Online Journal)
Background: Nail aesthetic procedures so far have been a neglected domain of nail medicine. With changing times, more people are getting sensitized towards nail enhancement; hence, there is an ever-increasing need for dermatologist driven aesthetic nail procedures. Discussion: The management of various nail disorders takes a long time and might not be very rewarding with regard to complete aesthetic improvement. The aesthetic procedures can be utilized to camouflage and provide some relief to the patient. These procedures could also be a treatment modality for various common conditions like brittle nails, onychotillomania, and other habit tic deformities. The aesthetic procedures that we discussed in this article include nail peels, gel nails, and lasers for aesthetic indications. Many side effects of these procedures have been reported in the literature. This can be attributed to the fact that these procedures are currently being done at salons and not by dermatologists. Conclusion: Nail peels are a useful modality for nail surface irregularities and can be safely recommended. Gel nail technique is simple and when done by a trained person can be used to benefit patients with superficial nail plate abnormalities to improve their quality of life. The usage of lasers in the aesthetic improvement of nails is still in a nascent stage.